Influenza vaccine compatibility among hospitalized patients during and after the COVID-19 pandemic - Fratty, Ilana S.; Jurkowicz, Menucha; Zuckerman, Neta; Nemet, Ital; Atari, Nofar; Kliker, Limor; Gur-Arie, Lea; Rosenberg, Alina; Glatman-Freedman, Aharona; Lustig, Yaniv; Mandelboim, Michal (Frontiers in Microbiology, 2024)
Introduction Following the significant decrease in SARS-CoV-2 cases worldwide, Israel, as well as other countries, have again been faced with a rise in seasonal influenza. This study compared circulating influenza A and B in hospitalized patients in Israel with the influenza strains in the vaccine following the 2021–2022 winter season which was dominated by the omicron variant. Methods Nasopharyngeal samples of 16,325 patients were examined for the detection of influenza A(H1N1)pdm09, influenza A(H1N1)pdm09 and influenza B. Phylogenetic trees of hemagglutinin were then prepared using sanger sequencing. Vaccine immunogenicity was also performed using the hemagglutination inhibition test. Results Of the 16,325 nasopharyngeal samples collected from hospitalized patients between September 2021 (Week 40) and April 2023 (Week 15), 7.5% were found to be positive for influenza. Phylogenetic analyses show that in the 2021–2022 winter season, the leading virus subtype was influenza A(H3N2), belonging to clade 3C.2a1b.2a.2. However, the following winter season was dominated by influenza A(H1N1)pdm09, which belongs to clade 6B.aA.5a.2. The circulating influenza A(H1N1)pdm09 strain showed a shift from the vaccine strain, while the co-circulating influenza A(H3N2) and influenza B strains were similar to those of the vaccine. Antigenic analysis coincided with the sequence analysis. Discussion Influenza prevalence during 2022–2023 returned to typical levels as seen prior to the emergence of SARS-CoV-2, which may suggest a gradual viral adaptation to SARS-CoV-2 variants. Domination of influenza A(H1N1)pdm09 was observed uniquely in Israel compared to Europe and USA and phylogenetic and antigenic analysis showed lower recognition of the vaccine with the circulating influenza A(H1N1)pdm09 in Israel compared to the vaccine.